Współczesna teologia moralna o szacunku dla ludzkiego embrionu w ujęciu Livio Meliny - Tomasz Kraj (Polonia Sacra)
The current age is witnessing the depreciation of the value of innocent human life in the context of medicine and biotechnology. A principal issue concerns human embryos which may be conceived unnaturally through in vitro fertilization. Some of them are destined to be born and lead normal lives. However the majority of them are killed either through the very procedure of IVF or subsequently as subjects of various forms of experimentation. The Roman Catholic Church strives to protect human embryos. Her moral teaching addresses the problem continuously; however the most fervent teaching concerning this problem is John Paul II’s encyclical letter Evangelium vitae. This encyclical explains the great value of innocent human life with reference to three fundamental theological statements: that the humans are the only beings created in God’s image and likeness, that they were redeemed by the passion, death, and resurrection of God’s Son, and that they are called to communion with God. This special relationship with God creates the human’s dignity and gives his life its particular value. Nobody has the authority to dispose of his/her life according to his/ her individual inclination any more than he has the authority to decide the same in the case of others. The life of any innocent human being which starts with conception may not be violated and nobody may be justified in killing innocent people. The killing of human embryos is the most common case of such killing in the current age.